Influencia de las condiciones de operación y del consorcio bacteriano en el rendimiento de las fermentaciones anaeróbicas tipo mixAlco (2017)
"The MixAlco process is a biorefining technology that transforms lignocellulosic residues into chemicals with high added value. This process uses an anaerobic fermentation stage to produce a mixture of volatile carboxylic acids that is converted into the desired products through conventional chemical reactions... This work focusses on the fermentation stage correlating the obtained carboxylic acids concentration with inoculum origin (either from a beach or from a salt mine), the lignocellulosic substrate (rice husk, coffee husk and sugarcane bagasse), the pretreatment type (no pretreatment, biological, alkaline with Ca(OH)2 or NaOH), the chemical compound to control pH (CaCO3 y MgCO3) and the use or not of dry nutrients." -- Tomado del Formato de Documento de Grado.